2012
DOI: 10.1021/nl302160d
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Chemical Route toward Monodisperse Iron Carbide Nanoparticles Displaying Tunable Magnetic and Unprecedented Hyperthermia Properties

Abstract: We report a tunable organometallic synthesis of monodisperse iron carbide and core/shell iron/iron carbide nanoparticles displaying a high magnetization and good air-stability. This process based on the decomposition of Fe(CO)(5) on Fe(0) seeds allows the control of the amount of carbon diffused and therefore the tuning of nanoparticles magnetic anisotropy. This results in unprecedented hyperthermia properties at moderate magnetic fields, in the range of medical treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
130
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(145 citation statements)
references
References 36 publications
10
130
4
1
Order By: Relevance
“…Another appealing core/shell system for hyperthermia is the one composed of Fe(soft)/FeC(hard) nanoparticles, which have revealed tunable magnetism as a function of the FeC shell. The results show that core/shell nanoparticles (with high M S and moderate K u ) exhibit superior properties to single phase Fe or FeC particles, with values of SLP up to 415 W/g [406]. Moreover, based on their large imaginary susceptibility (indicating large magnetic losses), CoFe 2 O 4 -NiFe 2 O 4 nanoparticles have also been proposed as possible hyperthermia agents [284].…”
Section: Biomedical Applicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Another appealing core/shell system for hyperthermia is the one composed of Fe(soft)/FeC(hard) nanoparticles, which have revealed tunable magnetism as a function of the FeC shell. The results show that core/shell nanoparticles (with high M S and moderate K u ) exhibit superior properties to single phase Fe or FeC particles, with values of SLP up to 415 W/g [406]. Moreover, based on their large imaginary susceptibility (indicating large magnetic losses), CoFe 2 O 4 -NiFe 2 O 4 nanoparticles have also been proposed as possible hyperthermia agents [284].…”
Section: Biomedical Applicationsmentioning
confidence: 98%
“…Actually, some of the basic properties which could be appealing for the use of core/shell nanoparticles as recording media have already been experimentally demonstrated. For example, (i) it has been demonstrated that T B can be easily increased by adding a surface layer of a hard material on a soft nanoparticle (soft/hard approach) [102,143,250], (ii) it has been shown that the coercivity (i.e., switching field) of hard nanoparticles is reduced when coupled to soft shells (hard/soft approach) [102,190], (iii) the possibility to form selfassembled arrays of core/shell nanoparticles [92][93][94]99,102,103,122,190,263,406] or (iv) possible graded anisotropy in core/shell nanoparticles [105]. Nevertheless, other critical features like large, defect free, self-assemblies of hard-soft core/shell nanoparticles (i.e., in the same range as the ones shown for single phase magnetic nanoparticles [407]) have not yet been demonstrated.…”
Section: Recording Mediamentioning
confidence: 99%
“…Employing NPs with optimized SAR values can substantially reduce the required doses, and therefore, many recent works have focused on the development of more efficient magnetic nanoheaters, such as exchange-coupled magnetic NPs (e.g., CoFe 2 O 4 @MnFe 2 O 4 ), 7 iron oxide nanocubes, 162,163 iron NPs, 164 and iron carbide NPs. 165 Interestingly, magnetosomes produced by magnetotactic bacterium have been reported to produce unusually large SAR values compared to similar magnetic NPs produced by synthetic colloidal methods. 166,167 This indeed indicates that there is still space for improving synthetic methods to produce more efficient materials.…”
Section: Magnetic Heatingmentioning
confidence: 99%
“…Measuring the hysteresis loop instead of performing temperature measurements presents two major advantages: i) the complete hysteresis loop shape contains much more information than its simple area : information on saturation magnetization, magnetic interactions, aggregation of MNPs, MNP anisotropy can for instance be deduced from the hysteresis loop shape. We and other groups have already shown the interest of this method to get an insight into the physics of magnetic hyperthermia [3,4,5,6]. ii) It is much faster than temperature measurements.…”
Section: Main Textmentioning
confidence: 99%
“…This is due to the fact that, at large frequencies, the signal is more sensitive to even slight modification of the position of the sample inside the sample holder. As a consequence, when this setup was used for measuring various nanoparticle systems, we have always restricted our frequency to a maximum value of 56 kHz [3,4,5].…”
Section: Measurements On An Iron Oxide Nanoparticle Ferrofluid A) Hymentioning
confidence: 99%